Pengaruh Kortikosteroid Terhadap Kontrol Glikemik Pasien Diabetes Mellitus Tipe 2: Systematic Review - Yusnita Julyarni Akri; Donna Dwinita Adelia; Donny n Yunamawan; Yanuar Hadi Irawan (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2026)
Corticosteroids are widely used drugs in a variety of clinical conditions and are known to affect glucose metabolism through increased gluconeogenesis and insulin resistance. In patients with Type 2 Diabetes Mellitus (DMT2), corticosteroid use has the potential to worsen glycemic control and increase the risk of hyperglycemia. However, the scientific evidence regarding the effect of corticosteroids on glycemic control in DMT2 patients is still scattered and varied, so a systematic review is needed. This systematic review aimed to evaluate the effect of corticosteroid use on glycemic control in DMT2 patients based on a narrative synthesis of available research results. Literature searches were conducted systematically on electronic databases PubMed, Scopus, ScienceDirect, and Google Scholar. The included studies included observational and experimental studies involving DMT2 patients receiving corticosteroid therapy, with outputs in the form of glycemic control parameters such as fasting blood glucose, postprandial blood glucose, and HbA1c. The selection of studies is carried out based on the inclusion and exclusion criteria that have been set. The methodological quality assessment of the study was carried out using relevant instruments, and the research results were synthesized narratively following the PRISMA guidelines. Most of the studies reviewed showed an increase in blood glucose levels and/or HbA1c in patients taking corticosteroids, particularly in the use of systemic corticosteroids with specific doses and durations. The variation in effects on glycemic control was influenced by the type of corticosteroid, route of administration, duration of therapy, and clinical characteristics of the patient. Some studies have also reported an increased need for antidiabetic therapy during corticosteroid use. Based on narrative synthesis, corticosteroid use tends to negatively impact glycemic control in Type 2 Diabetes Mellitus patients.